2020
DOI: 10.48550/arxiv.2005.11683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulse replication and accumulation of eigenvalues

Abstract: Motivated by pulse-replication phenomena observed in the FitzHugh-Nagumo equation, we investigate traveling pulses whose slow-fast profiles exhibit canard-like transitions. We show that the spectra of the PDE linearization about such pulses may contain many point eigenvalues that accumulate onto a union of curves as the slow scale parameter approaches zero. The limit sets are related to the absolute spectrum of the homogeneous rest states involved in the canard-like transitions. Our results are formulated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(69 reference statements)
2
3
0
Order By: Relevance
“…Here of course the heterogeneity at ξ = 0 precludes such a mode, but as ε 1 0, we found that the associated eigenfunction is localised near the front interface at ξ = ξ tf , which moves farther and farther away ξ = 0 as c c lin , and approximately resembles the spatial derivative of the front. We note that similar behaviour can be observed for the standard Fitzhugh-Nagume pulse with a small 'critical' eigenvalue resembling an approximate spatial derivative of the Nagumo pulse along the back, see [11] for numerical computations.…”
Section: Numerical Results and Evidencesupporting
confidence: 75%
See 1 more Smart Citation
“…Here of course the heterogeneity at ξ = 0 precludes such a mode, but as ε 1 0, we found that the associated eigenfunction is localised near the front interface at ξ = ξ tf , which moves farther and farther away ξ = 0 as c c lin , and approximately resembles the spatial derivative of the front. We note that similar behaviour can be observed for the standard Fitzhugh-Nagume pulse with a small 'critical' eigenvalue resembling an approximate spatial derivative of the Nagumo pulse along the back, see [11] for numerical computations.…”
Section: Numerical Results and Evidencesupporting
confidence: 75%
“…At the phenomenological level, our result shows the somewhat subtle and unexpected phenomena of a (spectrally) stable pattern-forming front with a long plateau state lying near an absolutely unstable base state. More generally, it contributes a novel and explanatory example to the recently growing set of works where absolute spectrum plays a role in governing the stability and bifurcation of coherent structures [11,14,21,57]. We note that our case is novel as we exhibit a situation where the absolute spectrum of the plateau state is unstable while the spectrum of the linearisation about the front is stable.…”
Section: Overview Of Our Approachmentioning
confidence: 75%
“…Here of course the heterogeneity at ξ = 0 precludes such a mode, but as ε 1 0, we found that the associated eigenfunction, being localized near the front interface at ξ = ξ tf , which moves farther and farther away ξ = 0 as c c lin , approximately resembles the spatial derivative of the front, and hence an approximate translational mode. We note that similar behavior can be observed for the standard Fitzhugh-Nagume pulse with a small "critical" eigenvalue resembling an approximate spatial derivative of the Nagumo pulse along the back, see [9] for numerical computations.…”
Section: Restriction To the Real Linesupporting
confidence: 74%
“…At the phenomenological level, our result shows the somewhat subtle and unexpected phenomena of a (spectrally) stable pattern-forming front with a long plateau state lying near an absolutely unstable base state. More generally, it contributes a novel and explanatory example to the recently growing set of works where absolute spectrum plays a role in governing the stability and bifurcation of coherent structures [9,12,51]. We note that our case is novel as we exhibit a situation where the absolute spectrum of the plateau state is unstable while the spectrum of the linearization about the front is stable.…”
Section: Overview Of Our Approachmentioning
confidence: 76%
“…An interesting extension of this work would be to calculate the Maslov index of a wave which passes through a fold point, e.g. [7].…”
Section: Introductionmentioning
confidence: 99%